Avaliação de um teste bioquímico de triagem para a detecção de indivíduos heterozigotos para a fenilcetonúria - ANDRADE, Roseani da Silva (Universidade Federal do Pará, 2012)
Phenylketonuria (PKU) is an inherited metabolic disease resulting from deficiency of the enzyme phenylalanine hydroxylase (PAH) that converts the amino acid phenylalanine into tyrosine. This study aimed to investigate the metabolism of amino acids phenylalanine (Phe) and tyrosine (Tyr) in heterozygotes for PKU, in fasting and after an overload of Phe (25 mg / kg) using different biochemical parameters (levels of Phe and Tyr and relations Phe / Tyr and Phe ² / Tyr), to identify the best variable to discriminate heterozygotes for PKU and normal subjects. The protocol used was the measurement of plasma Phe and Tyr in the case of fasting, 30, 45, 60 and 90 minutes after the overload of Phe at a dose of 25mg/kg. The sample consisted of 50 individuals, 23 binding heterozygotes (10 men and 13 women) and a control group of 27 healthy individuals (13 men and 14 women), according to the matching criteria: gender and age (18 to 44 years) . To analyze the effect of an overload of Phe in each group, the results of the parameters Phe, Tyr, Phe / Tyr and Phe2/Tyr after overload were compared with those observed in the fasting state. Statistical inferences were performed between groups in longitudinal and transverse aspects and applied the Student t test, Wilcoxon test, Student test and its equivalent nonparametric test and the Mann-Whitney test. Evaluating the ROC curve of the variables used, the three best parameters to classify heterozygous and normal subjects were: the dosage of Phe 45 and 90 minutes, as well as the result of micromolar Phe2/Tyr fraction after 90 minutes of overload. The discriminant function showed 86% accuracy and a correct classification of 94.4% of individuals heterozygous for PKU.